Cardiac imaging in tafamidis-treatment patients with transthyretin amyloid cardiomyopathy. (14th October 2021) - Rettl, R; Mann, C; Duca, F; Dachs, T.-M; Binder, C; Kronberger, C; Schrutka, L; Dalos, D; Dona, C; Kammerlander, A; Beitzke, D; Charwat-Resl, S; et al.
Abstract: Background: Tafamidis kinetically stabilizes the tetrameric form of transthyretin (TTR) and thus may halt disease progression in patients with transthyretin amyloid cardiomyopathy (ATTR-CM). In our explorative analysis, we aimed to investigate the treatment effect on functional capacity and cardiac biomarkers as well as cardiac function and structure using echocardiography and cardiac magnetic resonance imaging (CMR), and to compare patients treated with tafamidis with an untreated control cohort. Methods: Consecutive ATTR-CM patients either received tafamidis 61mg (n=64) or tafamidis 20mg (n=23) or were assigned to an untreated control cohort (n=54) reflecting the natural history of the disease. Subsequently, we performed clinical, laboratory, echocardiography and CMR follow-up at a median of 9 to 12.5 months. Results: Main results are summarized in Table 1. In brief, we observed evidence of improvement in functional capacity as measured by the 6-minute walk distance (6MWD) in tafamidis 61mg treated patients (baseline: 377.1m vs. follow-up: 383.2m, p=0.678) compared to a significant decline in mean 6MWD in untreated patients (388.1m vs. 336.4m, p=0.002; cohort comparison: p=0.005). Analysis of cardiac biomarkers revealed evidence of therapeutic response by a decrease in median NT-proBNP levels in patients treated with tafamidis 61mg (2633.0pg/mL vs. 2244.0pg/mL, p=0.366), whereas a significant increase was observed in untreated patients (2798.0pg/mL vs. 3422.0pg/mL, p<0.001; cohort comparison: p<0.001). Echocardiographic findings revealed evidence of approximate stabilization in mean left ventricular (LV) strain (−11.75% vs. −11.58%, p=0.534) and mean right ventricular (RV) strain (−14.18% vs. −13.72, p=0.377) in the tafamidis 61mg treatment cohort compared to significant deterioration of mean LV longitudinal function (−11.71% vs. −10.59%, p=0.001) and mean RV longitudinal function (−14.36% vs. −12.99%, p=0.038) in the untreated cohort (cohort comparison: p=0.030 and p=0.269). Furthermore, cardiac structural assessment by CMR showed a significant increase in mean LV mass (199.1g vs. 214.3g, p=0.040) and mean extracellular volume (50.52% vs. 55.96%, p=0.026) in untreated patients, suggesting increased progression of myocardial amyloid deposition. Conclusion: Treatment with tafamidis in patients with ATTR-CM results in significant improvements in functional capacity and cardiac biomarkers, and shows marked benefits in functional as well as structural imaging parameters compared with an untreated control cohort. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Pfizer Inc.